PENGARUH PENGGUNAAN AROMATERAPI CHAMOMILE TERHADAP TINGKAT KECEMASAN PADA PASIEN PREOPERASI INSISI DAN EKSISI PADA PAYUDARA - Amalia Khoirun Nisa; Fiashriel Lundy; Imam Subekti (Poltekkes Kemenkes Malang, 2020)
Growth or development of abnormal body cells in the breast. The action for treatment is to undergo surgery. The problem that arises before surgery is anxious as a response to the patient's anticipation of action. One worry management is using aromatherapy. This study aims to determine the differences in anxiety levels before and after given chamomile aromatherapy in patients preoperatively suspect breast at Karsa Husada Batu Hospital. The research method used is non probability sampling type purposive one group sampling pretest post test. The research subjects were preoperative patients suspect breast as many as 31 respondents. The instrument used to determine anxiety in this study was the Zung questionnaire. Before being given aromatherapy, there were 26 anxiety respondents (86.6%) and 4 mild anxiety respondents (13.3%). After being given aromatherapy there was a decrease in the level of anxiety, with mild anxiety of 28 respondents (93.3%) and moderate anxiety of 2 respondents (6.66%). The statistical test used was the Wilcoxon test which showed that there were significant differences before and after being given aromatherapy at the anxiety level with p-value is 0,000. The conclusion is the influence in using chamomile aromatherapy on the anxiety of patients pre-incision and excision surgery in the breast at Karsa Husda Batu Hospital. Recommendations for patients are to use chamomile aromatherapy can be used to reduce pre and postoperative anxiety. Keywords: Aromatherapy, Anxiety, Incision and Excision, Breasts